Anticipating Large and Widespread Seasonal Deprivation in the Sahel - Lain, Jonathan (Washington, DC : World Bank, 2022)
In addition to being regularly confronted with unpredictable shocks such as floods, droughts, or conflicts, Sahelian households have to deal with the effects of seasonality. This leads to a significant reduction in food and non-food consumption across the season, exposing the poor to transient food insecurity and malnutrition.